2017
DOI: 10.1007/s00216-017-0257-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel two-step sequential bioaccessibility test for potentially toxic elements in inhaled particulate matter transported into the gastrointestinal tract by mucociliary clearance

Abstract: A novel two-step sequential extraction has been developed to assess the bioaccessibility of As, Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn in airborne particulate matter following inhalation and transport into the human gastrointestinal tract by mucociliary clearance. A new artificial mucus fluid (AMF) was used to determine the bioaccessible potentially toxic element (PTE) fraction in the upper airways, in sequence with the simplified bioaccessibility extraction test (SBET) or the stomach phase of the unified bioaccess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This approach could be emulated when developing a lung model. Versions of this approach have already started to be reported, including an inhalation-ingestion bioaccessibility assay (Kastury et al 2018b(Kastury et al , 2020 and mucus-oral extraction test (Alpofead et al 2017). While promising, the implications of a sequential strategy on the calculation of a dissolution coefficient would have to be considered as this may limit the comparability of the data obtained to historical information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach could be emulated when developing a lung model. Versions of this approach have already started to be reported, including an inhalation-ingestion bioaccessibility assay (Kastury et al 2018b(Kastury et al , 2020 and mucus-oral extraction test (Alpofead et al 2017). While promising, the implications of a sequential strategy on the calculation of a dissolution coefficient would have to be considered as this may limit the comparability of the data obtained to historical information.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that compared to long-term extraction in SLF, or simulated gastric fluid alone, metal(loid) bioaccessibility increased significantly when inhalation and ingestion pathways were combined. In another approach, particulate matter samples were incubated in artificial mucus fluid prior to oral bioaccessibility extraction tests to investigate the release of potentially toxic metal ions (Alpofead et al 2017). This simulated the deposition and transport of particulates from the mucociliary escalator in the respiratory tract to the GIT.…”
Section: Simulated Biological Fluid Specificity To Environmentsmentioning
confidence: 99%
“…Despite the well-studied pulmonary effects of ambient PM, little is known about its effects on the gastrointestinal tract and microbiome. Ambient PM can enter gastrointestinal tract through the bloodstream or by ingestion, either after clearance via airway cilia or by consumption of contaminated food and water [10,11]. Salim et al and Beamish et al proposed a model of PM-induced intestinal and systemic in ammation, suggesting that PM in the gastrointestinal tract causes oxidative stress and increases gut permeability [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Gut exposure to air pollutants occurs via mucociliary transport of PM from the respiratory tract and by ingestion of food and water [10,11], suggesting that the steady-state concentrations of PM in the gut may mirror concentrations in the lung. We hypothesized that chronic exposure to ambient particulate matter induces gut microbial dysbiosis in a rat COPD model.…”
Section: Introductionmentioning
confidence: 99%
“…Further development of this procedure will involve applying DGT to real air filter samples. In a continuation of work reviewed 1 last year, researchers in Scotland proposed 26 the use of a novel two-step sequential-extraction procedure to assess the biaccessibility of As, Cd, Cr, Cu, Fe, Mn, Pb and Zn in urban air particulate matter. A new artificial mucus fluid extractant was applied to samples followed by either the SBET or the stomach phase of the UBMG so enabling metal bioaccessibility fractions in both the upper airways and the stomach to be determined.…”
Section: Sample Preparationmentioning
confidence: 99%